An Indentation Method for Determining the Elastic Modulus, Hardness and Film Thickness of a Tri-Layer Materials - Zhao, S.; Li, Y.; Zhang, J.; Wang, B.; Zhao, M.; Lu, Chunsheng (2024)
Multilayer materials have found extensive application within the aerospace industry due to their notable mechanical attributes. The operational longevity and dependability of such materials are substantially influenced by the performance characteristics of individual layers. In this study, an indentation method was established for employing a weighting function to simultaneously characterize the elastic modulus, hardness and film thickness of tri-layer materials. The results of numerical simulations indicate that incorporating the substrate effect in such an approach allows for precise assessment of the mechanical properties of tri-layer materials with diverse thicknesses. To validate the method, nanoindentation tests were performed using two tri-layer materials (i.e., Al/Cu/304SS and Cu/Al/304SS). Further, according to numerical and experimental data, the proposed model could be reduced to evaluate the mechanical properties of a bilayer material. The present findings demonstrate the effectiveness and applicability of the proposed indentation method in characterizing multilayer materials, facilitating reliable assessment in practical applications.